The Role of Whatsapp Business in Increasing Consumer Engagement by Implementing Dewa Eka Prayoga Marketing Techniques - Sayudin, Sayudin; Kartono, Kartono; Curatman, Aang (Journal of World Science, 2024)
WhatsApp Business has become a crucial communication tool for many businesses, enabling direct and efficient customer interactions. This study uses Riviera Publishing as a case study to analyze the role of WhatsApp Business in driving engagement, satisfaction, and loyalty to increase customer numbers. Specifically, it examines how Riviera Publishing utilizes WhatsApp Business, loyalty, and satisfaction strategies to impact customer growth. The research employs a quantitative method, collecting data through online surveys among active Riviera Publishing customers who use WhatsApp Business. A simple random sample was selected from the customer population, and structured questionnaires were used to gather data on customer experiences with WhatsApp Business. Data were analyzed using descriptive statistics and regression techniques. The results indicate that WhatsApp Business engagement significantly enhances customer numbers through more responsive and personalized interactions, boosting customer satisfaction with Riviera Publishing’s services and reinforcing loyalty. Additionally, the use of WhatsApp Business contributes to customer growth through more effective marketing strategies and a broader reach. This study concludes that WhatsApp Business is not merely a communication tool but also an effective strategy for building closer customer relationships, which is essential for business growth and success. The practical implications of the research include the development of advanced digital marketing strategies and enhancing customer service based on direct and responsive interactions via the WhatsApp Business platform.